Dumb – Bell Shape Penis - Dr. U.H. Vyas; Dr. Jayesh Brambhatt; Dr. Santosh C. Raibagkar (Indian Journal of Plastic Surgery)
An unusual complication following religious circumcision resulting in urethral fistula is reported.